METHODOLOGY OF CREATING PROBLEM SITUATIONS THROUGH THE STEAM APPROACH IN PRIMARY EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The rapid development of science and technology has led to the modernization of educational systems worldwide. In this context, the STEAM (Science, Technology, Engineering, Arts and Mathematics) approach has become an important pedagogical innovation, especially in primary education. One of the core elements of STEAM is the creation of problem situations that stimulate pupils’ cognitive activity, critical thinking, and creativity. This article analyzes the methodology of creating problem situations through the STEAM approach in primary education. The study explores theoretical foundations, pedagogical principles, and practical methods of implementing problem-based STEAM activities in primary classrooms. The results demonstrate that STEAM-based problem situations significantly enhance pupils’ motivation, collaborative skills, and problem-solving abilities.